Effect of Hydrogen on the Formation of Structure and Mechanical Properties of the Ultrafine-Grained Titanium Alloy of Ti-Al-V-Mo System - Grabovetskaya G. P.; Mishin I. P.; Zabudchenko O. V.; Stepanova E. N. Ekaterina Nikolaevna; Khovanova A. O. (2018, 2018)
Title screen